Hydrothermally treated coral scaffold promotes proliferation of mesenchymal stem cells and enhances segmental bone defect healing - Huang, Jianping; Park, Jaehan; Jung, Narae; Moon, Hong Seok; Zong, Zhixian; Li, Gang; Lin, Sien; Cho, Sung-Won; Park, Youngbum (Frontiers in Bioengineering and Biotechnology, 2023)
Synthetic hydroxyapatite (HAp) scaffolds have shown promising therapeutic outcomes in both animals and patients. In this study, we aim to evaluate the chemical and physical phenotype, biocompatibility, and bone repair effects of hydrothermally treated coral with natural coral and synthetic HAp. The phase composition, surface pattern, 3D structures, and porosity of the scaffolds were characterized, and cell viability, proliferation, and osteogenic differentiation of mesenchymal stem cells (MSCs) after seeding onto the scaffold were determined. The scaffolds were implanted into rats to assess their bone repair effects using micro-CT analysis, mechanical testing, and histological staining. The results showed that the phase composition, porous structure, and porosity of hydrothermally treated coral were comparable to pure HAp scaffold. While only the natural coral happens to be dominantly calcium carbonate. Higher cell proliferation and osteogenic differentiation potential were observed in the hydrothermally treated coral scaffold compared to natural coral and pure HAp. Histological results also showed increased new bone formation in the hydrothermally treated coral group. Overall, our study suggests that hydrothermal modification enhances the cytocompatibility and therapeutic capacity of coral without altering its physical properties, showing superior effectiveness in bone repair to synthetic HAp.